Generalized moment representations and the Pade-Chebyshev approximations - Golub, A. P. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
An approach to the application of Dzyadyk’s generalized moment representations in problems of construction and investigation of the Padé-Chebyshev approximants is developed. With its help, certain properties of the Padé-Chebyshev approximants of a class of functions that is a natural analog of the class of Markov functions are studied. In particular, it is proved that the poles of the Padé-Chebyshev approximants of these functions lie outside their domain of analyticity.